THE UNIVERSAL AND FAIR ACCESS TO PUBLIC WATER SUPPLY SERVICE - Ștefan, Elena Emilia (International Journal of Legal and Social Order, 2024)
This paper focuses on one of the most important issues of our time, namely access to water. Currently, in relation to climate change, on a global level we can talk about a water crisis, to which public authorities on all continents must find solutions. The reason for our analysis is a news story from August 2024 that appeared in the mass media, according to which almost 600 localities have restrictions in the supply of drinking water. Therefore, this worrying information made us curious to document this topic. The scope of the paper is to investigate, from an interdisciplinary point of view, the way in which the legislator deals with the issue of access to public water supply services, from a national perspective but also from a comparative law perspective. The research can contribute to enriching the literature and developing the state of the art on the issue, supporting authorities to identify new solutions for access to water services for the whole society. By way of law-specific research methods, the conclusion of the paper will be that on the one hand, the state must guarantee access to water for citizens and on the other hand, people must respect the law and be more responsible towards water. The result of the research shows that the administration is at the service of the citizen so that water services provided to the population must be carried out effectively in order to make sure that water is available for as many people as possible